Mind Mapp Model of Religious Education Learning in Improving Reading Ability to Read The Al-Qur'an - Yunus Yunus (Indonesian Journal of Instructional Media and Model, 2020)
Acquired Data source of that student covers, formative student essay in work problem that is given at the early cycle. Observation sheet result to measure the result step-up studies student with implemented a model of Information proceedings. The study is executed with Classroom Action Research (CAR). This research is executed at STMIK Eresha with the subject of research student total of 53 students. The implementation of the Mind Mapping learning model in the Islamic Religious Education subject is quite good.  The results showed that at the first meeting the highest percentage of students who answered could reach 96%. Whereas in the second test, it was 97% at the 13-15 meeting. Based on the data, the 13-15 meeting material discussed was the animal excretion system, students felt more difficult with the material than the previous material. The data from the questionnaire results of student responses to the implementation of learning using a learning mind map today can motivate students to learn read the Qur'an. The highest percentage of students who answer can be achieved, reaching 83% at the 7-9th meeting.   Most of the students were actively involved in making Mind Mapping. Collaboration is also carried out to make the best Mind Mapping. Student response to the Mind Mapping learning model is also very high. Most of the students felt interested and challenged to make Mind Mapping, although there were a few students who were less happy about the Mind Mapping learning model.